(EFL) Learners’ Perspectives on Vocabulary Learning through Reading and Listening - Sara Jamal Mohammed Faraj (International Journal of Social Sciences & Educational Studies)
Many learners of English as a foreign language may encounter difficulties in terms of acquiring new vocabulary items. These difficulties could be owed to the various forms, meanings, usages of words, and lack of exposure to the words of languages explicitly. Language skills in general and the two receptive skills of reading and listening in particular are of the most important value in enhancing new lexical items. The present study aimed at investigating the EFL students’ perspective on vocabulary learning via reading and listening skills. In doing so, 49 undergraduate Kurdish EFL learners were the subjects of the study who were third-year students and were from the Department of English Language-Faculty of Education at Koya University. To collect the data, a questionnaire of 14 items for both listening and reading skills was administered. The results showed that the participants’ attitudes were positive in vocabulary development through reading and listening skills. It was also found that there is no significant difference between both genders and age groups in vocabulary learning.